Development of Character Value Based Teaching in Rafly Song Song Lyrics For Students Class VIII Madrasah Tsanawiyah Private Vocational School of Langsa City - Lucy Lestari; Biner Ambarita; Daulat Saragi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to produce teaching material products in the form of poetry writing modules based on character values in the lyrics of the song Rafly Kande and describe their eligibility. The development module makes it easier for students to learn about writing poetry. This research uses research and development methods or Research and Development (R & D). The product that was developed based on preliminary research is the character development writing module based on character values in the lyrics of the song Rafly Kande for grade VIII students which contains poetry understanding materials, poetry builder's elements, character values, character values in the Rafly Kande song. The test subjects in this research development are subject matter experts, namely material experts, design experts and teachers. As well as the subject of students of class VIII Madrasah Tsanawiyah Private Geudubang Aceh Langsa as prospective module users. The determination of the subject was carried out by random sampling, consisting of 3 students for individual tests, 9 students for small group tests and 32 students for limited field tests. Data collection techniques are done by anget. This questionnaire is used to assess modules developed from the aspects of module completeness, material content and physical appearance of the module. The results showed that in the individual test the writing module of poetry based on character values in the lyrics of the song Rafly Kande was included in the feasible category after the revision, the result of the development module was included in the small group test and the result of the development module was in the very feasible category in the limited field test. Thus, the development module for writing character-based poems in the lyrics of the song Rafly Kande for students of class VIII results of this development is appropriate for students to use.